Drivers of Density in Ornate Tree Lizards (Urosaurus ornatus) - Paterson, James (Université d'Ottawa / University of Ottawa, 2017)
Explaining spatial and temporal variation in the abundance of species is one of the primary goals of ecology. Habitat selection, the behaviour that organisms use to choose habitat patches that maximize fitness, can explain patterns in abundance between patches at small spatial scales within the dispersal capacity of the species. However, habitat selection models assume there is a reduction in individual fitness as population density increases due to increased competition between individuals. Ectotherms, which often select habitats based on temperature, a density-independent resource, may not display density-dependent responses if temperature limits energy assimilation more than finite food resources limit energy acquisition. As predicted by their dependence on environmental temperatures, some ectotherms select habitat largely independently of population density when temperatures are far from the optimal temperature for performance. But, is density-dependence prevalent in ectotherm populations when temperatures are close to the optimal temperature for performance? Habitat selection models also assume that all individuals of a population exhibit the same strategy for maximizing fitness through habitat selection. However, differences in morphology and behaviour (e.g., reproductive strategy) can modify the optimal habitat selection strategy for different phenotypes. Finally, observed patterns in habitat selection and abundance can also be modified by competition with other species. Quantifying the relative importance of these different factors that affect habitat selection behaviour will improve our ability to predict the spatial distribution and relative abundance of organisms. The objective of my thesis was to explain spatial variation in the abundance of ectotherms, using the ornate tree lizard (Urosaurus ornatus) as a study species. In chapter one, I tested whether density-dependent habitat selection explained patterns in abundance and fitness of lizards between two habitats differing in suitability. In chapter two, I tested whether density dependent habitat selection in tree lizards was caused by intraspecific competition for food that limited body size and growth. In chapter three, I tested whether variation in reproductive strategy, as indicated by throat colour phenotype, affected space use and habitat selection in male tree lizards. Finally, in chapter four, I tested whether interspecific competition with another lizard species affected habitat selection, fitness, and abundance of tree lizards. My thesis emphasizes the importance of intraspecific competition in shaping patterns of habitat selection and abundance in terrestrial ectotherms. I show that habitat selection is strongly density-dependent despite differences in thermal quality between habitats. I show that density-dependent mortality and growth lower the fitness of individuals when populations reach high densities, and this likely caused habitat selection to be density-dependent. Despite this evidence for density-dependent habitat selection, I show considerable variation between individuals in habitat selection and space use. Males with different throat colour phenotypes select habitats differently, demonstrating that variation in morphology can influence habitat selection patterns within a population. Finally, I show that interspecific competition with another lizard affects space use and how frequently tree lizards switch habitats, but this does not lead to differences in fitness or in the relative abundance of tree lizards in habitats. Therefore, intraspecific competition for resources was the dominant force shaping the relative abundance of tree lizards in different habitats.
Keywords: Density; Habitat selection; Ectotherm; Mark-recapture; Ideal Free Distribution; Competition